2020
DOI: 10.1097/olq.0000000000001176
|View full text |Cite
|
Sign up to set email alerts
|

Pubic Hair Grooming and Sexually Transmitted Infections: A Clinic-Based Cross-Sectional Survey

Abstract: Background: Pubic hair grooming has been correlated with a selfreported history of sexually transmitted infections (STIs). We examined this relationship further in a cross-sectional survey of patients attending an urban STI clinic in San Francisco in 2018.Methods: Pubic hair grooming practices and detailed sexual histories were obtained. Sexually transmitted infections were confirmed via laboratory diagnosis or physical examination by a licensed provider.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Furthermore, as the number of women who undergo elective genital surgeries increases, it is essential that researchers and clinicians better understand how women view their genital appearance before undergoing surgery (such as a labiaplasty) relative to their PHG behaviours 7,16 . A woman with completely removed PH may consider genital surgery when evaluating her genitalia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, as the number of women who undergo elective genital surgeries increases, it is essential that researchers and clinicians better understand how women view their genital appearance before undergoing surgery (such as a labiaplasty) relative to their PHG behaviours 7,16 . A woman with completely removed PH may consider genital surgery when evaluating her genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, sex workers had completely removed their PH to reduce parasite transmission such as pubic lice or for medical reasons associated with sexually transmitted infections (STIs). Recent studies have also provided significant correlations between PHG and sexual activity relative to STIs 16 . Gaither et al reported that after adjusting for age, individuals who groomed their anus were 3.1 times as likely to be diagnosed with a rectal STI compared with genital‐only groomers and non‐groomers 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study population for this analysis is a subcohort from another initial, published study that evaluates the association between pubic hair grooming and STI diagnosis. 16 In that study, eligible participants were identified amongst individuals visiting the San Francisco Department of Public Health City Clinic between April and May of 2018 based on the inclusion criteria: primary English speaker, age ≥18. From those eligible in the initial study, the informed consented participants who completed the survey and reported receptive anal sex in the past 3 months were eligible for this secondary post-hoc analysis.…”
Section: Methodsmentioning
confidence: 99%